PENGARUH MASASE KAKI DENGAN MINYAK SEREH WANGI TERHADAP PENURUNAN TEKANAN DARAH HIPERTENSI LANSIA DI KOTA PEKALONGAN - Indar Widowati; Afiyah Sri Harnany; Zaenal Amirudin, Rr.Sri; Rr. Sri Sejati (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2014)
Increased life expectancy, causes the increase of the elderly population that have an impact on the shift  of  disease  pattern  from  infectious  diseases  to  degenerative  diseases  such  as  hypertension  . Treatment of  hypertension can be done in a  way that is pharmacological  with anti-  hypertensive drugs or non- pharmacological is with lifestyle modification or it could be a combination of both. Therapeutic massage is one of the non- pharmacological therapies that can reduce hypertension . Massage techniques at some point to remove the blockage in the blood so that blood and energy flow  in  the  body  back  smoothly  .  This  study  aims  to  determine  the  effect  of  foot  massage  with citronella oil to decrease blood pressure of elderly hypertensive patients . This type of research is the  study  randomized  pre  -  post  test  design  with  control  "  as  many  as  14  respondents  were recruited in this study , 7 respondents are citronella oil group and 7 respondents as a control group . The results  showed a decrease in  mean blood pressure before and after the  foot  massage using lemongrass oil , is systolic blood pressure by 9.09 mmHg and 5.71 mmHg for diastolic . While in control of a decrease in mean blood pressure before and after the foot massage using the control , is systolic blood pressure of 7.62 mmHg and diastolic 5.00 mmHg  Keywords : Massage feet , citronella oil , blood pressure